A case of canine Salmonella spp. osteomyelitis with secondary fracture following dog bite. Issue 5 (10th July 2021) - Williams, Elroy; Towle, Heather Ann Marie
Abstract: An immature canine was attacked by another dog in a kennel facility and sustained multiple wounds to the lateral right forelimb and cranial right lateral thoracic region. General surgical and antimicrobial therapies were instituted immediately. The patient battled with recurrent infections and subsequent delayed healing. After approximately 35 days from the initial injury, the patient became acutely lame and febrile. The persistently open wounds were cultured and returned positive for Salmonella spp . Within the following days, the patient became painful, and the lameness progressed significantly. Radiographs confirmed pathologic humeral fracture, and the patient was referred for specialty evaluation. Zoonotic preventative protocols were adopted at the specialty facility upon arrival. Complete forequarter limb amputation was curative in this patient. Abstract : An immature canine was attacked by another dog in a kennel facility and sustained multiple wounds to the lateral right forelimb and cranial right lateral thoracic region. The patient battled with recurrent infections and subsequent delayed healing and after approximately 35 days from the initial injury, the patient became acutely mildly lame and febrile. Open wounds and draining tracts were cultured and returned positive for Salmonella spp .; within the following days, the patient became painful, and the lameness progressed significantly, with radiographic confirmation of a pathologic humeral fracture.